Frontispiece: Hierarchical Metal Sulfide/Carbon Spheres: A Generalized Synthesis and High Sodium‐Storage Performance. Issue 22 (20th May 2019) - Shen, Laifa; Wang, Yi; Wu, Feixiang; Moudrakovski, Igor; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : Sodium‐Ion Batteries In their Communication on page 7238 ff., Y. Yu and co‐workers describe the formation of hierarchical carbon‐coated V2 S3 spheres with high sodium‐storage capacity through the thermal sulfurization of metal glycerate spheres.